Semiconductor-insulator-semiconductor (SIS) structures for high-performance optical modulation - Han, Jae-Hoon; Takenaka, Mitsuru; Takagi, Shinichi (23RD OPTO-ELECTRONICS AND COMMUNICATIONS CONFERENCE (OECC2018), 2018)
Material engineering for semiconductor-insulator-semiconductor (SIS) structures is important for a high-performance optical modulator. We have suggested an InGaAsP/Si hybrid SIS structure using direct wafer bonding with high-k dielectrics for using high electron effect in InGaAsP.